Psychotherapists’ experiences of working with religion and spirituality in psychotherapy - Filmer, Linda (University of the Witwatersrand, Johannesburg, 2025)
Recent research indicates an increasing demand for psychotherapists to attend to the religious and spiritual needs of their clients in an ethical and growth-promoting way. This study’s primary objective was to investigate the experiences of psychotherapists in navigating religion and spirituality in the therapy room. This research highlighted the complex nature of navigating religion and spirituality in therapy, foregrounding the need for spiritual competency, self-awareness and dialogue. This research was structured qualitatively, using open-ended semi-structured interviews to collect data. Psychologists registered with the HPCSA were asked to voluntarily participate in one-on-one interviews. Participants needed to have clinical experience of working with religion/spirituality in therapy, and were required to have practised for at least one year after fully qualifying. A sample of eight participants was interviewed. Transcribed interviews were analysed using Thematic Analysis (TA). Significant themes that arose from analysis of the data included: areas of opposition and rapprochement between the domains of religion/spirituality and psychotherapy; ways in which religion/spirituality could be experienced as helping or hindering for psychological growth and the therapeutic process; ways of engaging with clients’ religious/spiritual material that preserved the therapeutic relationship and honoured the clients’ belief system; significant tension and discomfort between the personal and professional roles of the psychotherapist in relation to religion/spirituality in therapy. Findings further suggest that there is a need for more training in the realm of spiritual competency, particularly given the fraught historical relationship between psychology and religion, the professional taboo of engaging with it, and the multi- religious, multicultural context of South Africa.
A research report submitted in fulfillment of the requirements for the Master of Art in Clinical Psychology, in the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; South Africa; religion; spirituality; psychotherapy; SDG-3: Good health and well-being; SDG-10: Reduced inequalities